2011
DOI: 10.1002/cncr.26149
|View full text |Cite
|
Sign up to set email alerts
|

Do multidisciplinary team meetings make a difference in the management of lung cancer?

Abstract: BACKGROUND: There is limited evidence regarding the effectiveness of multidisciplinary team (MDT) meetings in lung cancer. The objective of this study was to compare the patterns of care for patients with newly diagnosed lung cancer who were presented at a lung cancer MDT meeting with the patterns of care for patients who were not presented. METHODS: All patients who had lung cancer newly diagnosed in South West Sydney (SWS) between December 1, 2005, and December 31, 2008, were identified from the local Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
163
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 161 publications
(172 citation statements)
references
References 33 publications
2
163
0
2
Order By: Relevance
“…All studies concluded that a multidisciplinary setting resulted in improved patient outcomes in terms of diagnosis and/or treatment planning [14][15][16][18][19][20][21][22][25][26][27][28][29][31][32][33][35][36][37]40,42], improvements in survival [15,17,21,23,[28][29][30]36,39,41], patient satisfaction [24,31,38] and clinician satisfaction as a consequence of teamwork communication and cooperation [15,34]. Evidence of improved survival was found for colorectal [15,17,28,36], head and neck [29,41], breast [39], oesophageal [21] and lung [30] cancer.…”
Section: Impact On Patient Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…All studies concluded that a multidisciplinary setting resulted in improved patient outcomes in terms of diagnosis and/or treatment planning [14][15][16][18][19][20][21][22][25][26][27][28][29][31][32][33][35][36][37]40,42], improvements in survival [15,17,21,23,[28][29][30]36,39,41], patient satisfaction [24,31,38] and clinician satisfaction as a consequence of teamwork communication and cooperation [15,34]. Evidence of improved survival was found for colorectal [15,17,28,36], head and neck [29,41], breast [39], oesophageal [21] and lung [30] cancer.…”
Section: Impact On Patient Outcomesmentioning
confidence: 99%
“…The studies documented two motivating principles: firstly, MDTs ensure more appropriate treatment through a preoperative review of imaging and pathology results [19,20,22,25,26,40,42]; and secondly, a multidisciplinary approach guarantees the most up-todate treatment for all cancer patients seen at the facility or discussed online [16,18,21,23,32,33,35,[38][39][40][41]53]. Other clinical-based goals included improving patients' quality of life [24,32,42,[53][54][55] and setting up a structured followup care plan [53,[59][60][61].…”
Section: Mdt Goals and Scope Of Practicementioning
confidence: 99%
See 3 more Smart Citations